Travel distance affects rates and reasons for inpatient visits after pancreatectomy. Issue 7 (July 2019) - Simpson, Rachel E.; Wang, Christine Y.; House, Michael G.; Zyromski, Nicholas J.; Schmidt, C. Max; Nakeeb, Attila; Ceppa, Eugene P.
Abstract: Background: Centralization of complex surgical care leads to increased travel distances for patients. We sought to determine if increased travel distance to the index hospital altered inpatient Visit rates following pancreatectomy. Methods: Pancreatectomies from 2013–2016 were reviewed retrospectively from a single high-volume institution. Travel distance for 936 patients was determined, and patients were grouped by 50-mile increments. Visits ( Observations or Readmissions ) and corresponding reasons were gathered. Results: 222 patients (23.7%) had a Visit to any hospital (AH) within 90 days postoperative; 195 (87.8%) were to the index hospital (IH). The <50 miles group had the highest Visit rate to AH (28.6% vs. 17.8% vs. 24.6%; P = 0.008) and the IH (26.9% vs. 15.2% vs. 20.6%; P = 0.002) compared to 50–100 and > 100 miles. This trend was statistically significant for Observations, but not Readmissions . Gastrointestinal (GI) complaints alone led to 20.7% patients requiring Visits to AH at 90-days, mostly in <50miles group for Visits and Observations at AH and IH. Conclusions: Patients closest to the IH had the highest Visit and Observation rate following pancreatectomy without affecting Readmission rate, with GI complaints as a driving factor. Inpatient education and outpatient symptom management may reduce repeat hospitalization.